54.4k views
0 votes
which expression is equivalent to -28x^2+35x ? F. 7x(4x+5) G.-7x(4x-5) H.7x(4x-5) J.-7x(4x+5) please explain w the steps

2 Answers

3 votes

Answer:

G

Explanation:

-28x² + 35x = -7 * 4 * x² + (-7)*(-5)*x

= -7x(4x - 5)

User Vbrgr
by
4.5k points
3 votes

Hey!!

Solution,

-28x^2+35x

take the common,

-7x(4x-5)

The answer is -7x(4x-5)

Here,

If we solve,

-7x(4x-5)

Then, the answer would be:

= -7x*4x+7x*5

= -28x^2+35x

Hope it helps

Good luck on your assignment

User Fahad Alrashed
by
4.7k points